2017
DOI: 10.1128/aac.02691-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pharmacokinetic and Pharmacodynamic Profiles of Antofloxacin against Klebsiella pneumoniae in a Neutropenic Murine Lung Infection Model

Abstract: Antofloxacin is a novel broad-spectrum fluoroquinolone under development for the treatment of infections caused by a diverse group of bacterial species. We explored the pharmacodynamic (PD) profile and targets of antofloxacin against seven Klebsiella pneumoniae isolates by using a neutropenic murine lung infection model. Plasma and bronchopulmonary pharmacokinetic (PK) studies were conducted at single subcutaneous doses of 2.5, 10, 40, and 160 mg/kg of body weight. Mice were infected intratracheally with K. pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…This study was the first testing of increasing Klebsiella, which belonged to Proteobacteria in RD infants. More recent studies suggested Klebsiella may contribute to inflammation (33,34), such as bronchitis, pneumonia, and meningitis (35). Therefore, it could be supposed that RD infection, as the major cause of the viral gastroenteritis might disrupt the gut microbiota and introduce more effects from Klebsiella.…”
Section: Discussionmentioning
confidence: 99%
“…This study was the first testing of increasing Klebsiella, which belonged to Proteobacteria in RD infants. More recent studies suggested Klebsiella may contribute to inflammation (33,34), such as bronchitis, pneumonia, and meningitis (35). Therefore, it could be supposed that RD infection, as the major cause of the viral gastroenteritis might disrupt the gut microbiota and introduce more effects from Klebsiella.…”
Section: Discussionmentioning
confidence: 99%
“…This potent activity has been observed in vitro and in vivo against both S. aureus and Mycobacterium tuberculosis (18,19). Our previous studies with antofloxacin showed a dose-dependent activity with prolonged postantibiotic effects against Klebsiella pneumoniae in a model of lung infection in neutropenic mice (20). Similar to other fluoroquinolones, the most predictive PK/PD index of antofloxacin associated with efficacy against E. coli was the free drug AUC/MIC (21,22).…”
Section: Discussionmentioning
confidence: 63%
“…Blood samples were obtained by retro-orbital puncture at the following times after dosing: 0.08, 0.25, 0.5, 0.75, 1, 2, 4, and 8 h. Plasma was isolated by centrifugation of the blood samples at 3,000 ϫ g for 10 min at 4°C. Antofloxacin concentrations in plasma were determined using liquid chromatography-tandem mass spectrometry (LC-MS/MS) as we have described previously (20). The assay limit of quantification (LOQ) and limit of detection (LOD) were 0.01 and 0.005 mg/liter, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations